Sosialisasi Makanan Bergizi Puding Daun Kelor (Moringa Oleifera) Pencegah Stunting Oleh Kelompok KKN Universitas Negeri Padang di Kelurahan Durian II Kecamatan Barangin Kota Sawahlunto - Irfan Oktavianus; Adissah Putri Herdianti; Amalia Sagita S. Rangkuti; M. Kevin Nur Syamsu; Nailul Hasanah; Rozalia Rozalia; Riki Afriansyah; Sukma Ramadhani; Wahyuni Wahyuni (Jurnal Kabar Masyarakat, 2024)
This article discusses the socialization and distribution of moringa leaf pudding as an effort to prevent stunting carried out by KKN Students of Padang State University in Durian II Village, Sawahlunto City. This activity aims to increase public knowledge about stunting and the benefits of moringa leaves for toddler nutrition. Socialization was carried out to mothers during posyandu activities by providing education about stunting and the nutritional content of moringa leaves. Students also made and distributed moringa leaf pudding to toddlers and mothers. As a result, the socialization and distribution of pudding received a positive response from mothers and children. The audience was interested in moringa leaf pudding and was interested in making it themselves. This activity is expected to increase awareness of the importance of balanced nutrition to prevent stunting, as well as provide alternative solutions to the use of local resources in the stunting eradication program in the area.